Electrosynthesis of C3 Alkoxylated Quinoxalin‐2(1H)‐ones through Dehydrogenative C–H/O–H Cross‐Coupling. Issue 11 (26th February 2020) - Jiang, Xinpeng; Yang, Liechao; Ye, Zenghui; Du, Xiaofan; Fang, Liyun; Zhu, Yu; Chen, Keda; Li, Jianjun; Yu, Chuanming
Abstract : A highly efficient electrochemically dehydrogenative C–H/O–H cross‐coupling between quinoxalin‐2(1 H )‐ones and alcohols was developed under mild conditions. Using different types of alcohols as solvent, various 3‐alkoxylated quinoxalin‐2(1 H )‐ones were synthesized in a simple undivided cell at room temperature. This novel electrochemical cross‐dehydrogenative coupling approach features broad functional group tolerance, metal‐ and oxidant‐free conditions, and moderate to good yields. Abstract : Various 3‐alkoxylated quinoxalin‐2(1 H )‐ones were synthesized in a simple undivided cell via electrochemically dehydrogenative C–H/O–H cross‐coupling between quinoxalin‐2(1 H )‐ones and alcohols under mild conditions.